Hubungan Antara Direct Marketing dengan Keputusan Pembelian Rumah Subsidi - Tovan Isdanov (Jurnal Riset Manajemen Komunikasi, 2022)
Abstract. To market housing products, one of the activities carried out by the Marketing Division of Bank BNI is to market BNI Griya products, namely Direct Marketing or direct marketing to BNI Griya's target consumers. However, it is not certain how much influence Direct Marketing has on purchasing decisions for BNI Griya products. For this reason, this study wants to know the relationship between Direct Marketing and the decision to purchase subsidized housing. The application of direct marketing has an effect on home buying decisions in increasing sales of housing products at BNI Griya. Therefore, the Bank as a whole must further enhance its direct marketing program as a marketing strategy. Based on the findings in this study, the direct mail program on direct mail received a low rating, this indicates that the sales and marketing team of BNI Griya must improve the direct mail program by trying to make brochures that offer more attractive offers. Overall, the direct marketing program that has been run by BNI Griya is in the high rating category, this shows that the implementation of direct marketing has been considered good. The implementation of direct marketing programs must optimize all the factors owned so that there is a balance of each factor and the dimensions of direct marketing. Abstrak. Untuk memasarkan produk perumahan, salah satu kegiatan yang dilakukan oleh Divisi Marketing Bank BNI adalah memasarkan produk BNI Griya yaitu Direct Marketing atau pemasaran langsung kepada target konsumen BNI Griya. Namun, belum dapat dipastikan seberapa besar pengaruh Direct Marketing terhadap keputusan pembelian produk BNI Griya. Untuk itu, penelitian ini ingin mengetahui hubungan Direct Marketing dengan keputusan pembelian rumah subsidi. Penerapan direct marketing berpengaruh terhadap keputusan pembelian rumah dalam meningkatkan penjualan produk perumahan di BNI Griya. Oleh karena itu, secara keseluruhan Bank harus lebih meningkatkan program direct marketing sebagai strategi pemasaran. Berdasarkan temuan dalam penelitian ini, program direct mail pada direct mail mendapat rating yang rendah, hal ini menunjukkan bahwa tim sales dan marketing BNI Griya harus meningkatkan program direct mail dengan berupaya membuat brosur penawaran yang lebih menarik. Secara keseluruhan program direct marketing yang telah dijalankan oleh BNI Griya berada pada kategori high rating, hal ini menunjukkan bahwa implementasi direct marketing sudah dinilai baik. Pelaksanaan program pemasaran langsung harus mengoptimalkan semua faktor yang dimiliki sehingga terjadi keseimbangan dari masing-masing faktor dan dimensi pemasaran langsung.